1988
DOI: 10.1016/0014-5793(88)80904-9
|View full text |Cite
|
Sign up to set email alerts
|

Topology of Na+,K+‐ATPase Identification of the extra‐ and intracellular hydrophilic loops of the catalytic subunit by specific antibodies

Abstract: To study the topology of Na+,K+‐ATPase monoclonal antibodies (MAbs) specific for membrane‐bound enzyme were produced. Using immunofluorescence staining of viable cells or smears of a pig kidney embryonic (PKE) cell line, two groups of MAbs were selected, namely those binding to extra‐ or intracellular portions of the α‐subunit. The extracellular location of peptide loop 804–841 linking the Vth and VIth intramembrane hydrophobic segments was proved using MAb VG2. Another MAb, IIC9, interacting with PKE cells on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

1989
1989
2002
2002

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 16 publications
(7 reference statements)
2
29
1
Order By: Relevance
“…Various models imply the a-subunit polypeptide chain to traverse the membrane bilayer 6-8 times 2 [ 14-161. Limited proteolysis of the membrane-bound enzyme [25] and immunochemical analysis of the LYsubunit topography in the membrane [26] showed that the a-subunit polypeptide chain spans the lipid bilayer seven times. The location of the N-terminus of the protein in the cytoplasmic region of the cell is generally accepted [5].…”
Section: Cdna Cloning and Protein Structurementioning
confidence: 99%
“…Various models imply the a-subunit polypeptide chain to traverse the membrane bilayer 6-8 times 2 [ 14-161. Limited proteolysis of the membrane-bound enzyme [25] and immunochemical analysis of the LYsubunit topography in the membrane [26] showed that the a-subunit polypeptide chain spans the lipid bilayer seven times. The location of the N-terminus of the protein in the cytoplasmic region of the cell is generally accepted [5].…”
Section: Cdna Cloning and Protein Structurementioning
confidence: 99%
“…As the o~3-isoform mRNA content is substantial in renal [7] and nerve tissues [6], the protein is assumed to enter the enzyme isolated from kidney as a minor component. The membrane-bound Na,K-ATPase from pig kidney outer medulla was subjected to ELISA with various dilutions of aKLH-I, aBSA-I and a-c~p999 [9]. (Only two amino acid substitutions Ile(ce)/Leu(a3) and Arg(ce)/Asn(~3) allowed supposition that the antibodies will recognize both enzyme isoforms equally well.)…”
Section: Resultsmentioning
confidence: 99%
“…Two peptides corresponding to the a3-subunit regions were synthesized following the solid-phase technique [9]. Peptide I was coupled to Keyhole limpet hemocyanin (KLH) and bovia© serum albumin (BSA) using glutaraldehyde and peptide II, coupled to KLH with N-succinimidyl 3-(2-pyridyldithio)prrpionate as described in [10].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations